Plasma technology applied in textile industry - Oliveira, Fernando R. (2014)
Plasma technology applied to textiles is a dry, environmentally and worker friendly method to achieve surface alteration without modifying the bulk properties of different materials. In particular, atmospheric non-thermal plasmas are appropriate because most textile materials are heat sensitive polymers and applicable in a continuous processes. In the last years plasma technology has become a very active, high growth research field, assuming a great importance among all available material surface modifications in textile industry. The main objective of this work is to present an update on the current state of art relating plasma technologies applied to textile industry. The main effects obtained by the application of plasma discharge and all the textile production chain such as: desizing, mercerization, dyeing, printing, composite and finishing will be superficially discussed.